Multi-objective optimization in learn to pre-compute evidence fusion to obtain high quality compressed web search indexes - Pal, Anibrata (2016)
Submitted by S??boia N??gila (nagila.saboia01@gmail.com) on 2016-07-29T14:09:40Z No. of bitstreams: 1 Diserta????o-Anibrata Pal.pdf: 1139751 bytes, checksum: a29e1923e75e239365abac2dc74c7f40 (MD5)